Heritage Tourism Governance in Yogyakarta, Indonesia: Analysis of Roles and Cross-Sectoral Strategies - Adrian, Maisarah Mitra; Setiawan, Anang; Fathani, Aqil Teguh; Adrian, Geby Fitrya (Universitas Muhammadiyah Yogyakarta, 2026)
Heritage tourism is an essential component of sustainable development, providing economic benefits while safeguarding cultural heritage. In the Special Region of Yogyakarta, this sector holds strong potential due to its rich historical and cultural assets. As one of Indonesia’s key tourism destinations with national and international recognition, Yogyakarta occupies a strategic role in shaping the direction of cultural tourism governance. Nevertheless, management remains challenging, characterized by limited cross-sectoral coordination and the absence of integrated strategies to balance economic development with cultural preservation. These challenges have become more urgent in the post-pandemic era, requiring both adaptive and inclusive government. Previous studies have largely concentrated on macro-level policies or short-term recovery strategies, leaving limited examination of how cross-sectoral governance operates at the regional level. This study addresses that gap by providing an in-depth analysis of heritage tourism governance in Yogyakarta. A qualitative descriptive approach was employed, with data obtained from interviews with officials of the Cultural and Tourism Offices, policy document analysis, and observation of promotional and educational activities. The findings reveal a division of roles: the Cultural Affairs Office has prioritized preservation through regulation, education, and core facilities, while the Tourism Office has emphasized economic development through capacity building, supporting facilities, and digital and print promotion. The study highlights the need for integrated policies, stronger cross-institutional coordination, and coherent promotional strategies to ensure sustainable governance that balances cultural preservation with economic growth in Yogyakarta.